Subsurface geological modeling of Corrientes province (NE Argentina) and its relationships with the Guaraní Aquifer system function - Mira, Andrés (2015)
From the integration results of geological and geophysical data, a subsurface geological model of the Corrientes province (Argentina) that allows visualizing its deep geological structure and how it affected the Guaraní Aquifer System (GAS) is presented. 44 boreholes, 21 geophysical surveys and 1366 depth data from a Bouguer gravity anomaly model have been used. The model was built from five layers easily distinguishable in the regional subsurface: basement, pre-GAS sediments (Paleozoic), GAS sediments (Triassic-Lower Cretaceous), basalts (Serra Geral Group, Lower Cretaceous) and post basaltic sediments. The resulting geometry shows a basement with a structural high, the Dorsal Asunci_on-Rio Grande, where the GAS and the basaltic layer are thinner and the Mesozoic sediments rise near the surface. It is an área prone to local recharge and regional discharge of the GAS and it is in line with the latest piezometry and groundwater chemical analysis. Furthermore, two important depocenters have been identified, Corrientes and Curuzú structural high blocks, with at least 3500 m of sedimentary and volcano-sedimentary deposits that suggest the existence of significant pre-carboniferous sediment units associated to ancient extensional structures of the early Paleozoic. The proposed model allows defining a lithostratigraphic column of Corrientes and gives new criteria to redraw the southwest limit of the GAS.